Translocations are induced in hematopoietic stem cells after irradiation of fetal mice. (24th November 2022) - Hamasaki, Kanya; Matsumoto, Tomoko; Cologne, John; Mukai, Mayumi; Kodama, Yoshiaki; Noda, Asao; Nakamura, Nori
Abstract: Although mammalian fetuses have been suggested to be sensitive to radiation, an increased frequency of translocations was not observed in blood lymphocytes from atomic bomb (A-bomb) survivors who were exposed to the bomb in utero and examined as adults. Since experiments using hematopoietic cells of mice and rats confirmed this finding, it was hypothesized that either irradiated fetal hematopoietic stem cells (f-HSCs) cannot generate exchange-type chromosomal aberrations or cells bearing induced aberrations are eliminated before the animals reach adulthood. In the present study, pregnant mice (12.5–15.5 days post coitum [dpc]) were irradiated with 2 Gy of X-rays and long-term HSCs (LT-HSCs) were isolated 24 h later. Multicolor fluorescence in situ hybridization (mFISH) analysis of LT-HSC clones proliferated in vitro showed that nine out of 43 (21%) clones from fetuses and 21 out of 41 (51%) clones from mothers bore translocations. These results indicate that cells with translocations can arise in mouse f-HSCs but exist at a lower frequency than in the mothers 24 h after X-ray exposure. Thus, it seems likely that translocation-bearing f-HSCs are generated but subsequently disappear, so that the frequency of lymphocyte translocations may decrease and reach the control level by the time the animals reach adulthood.